Public MTs Students Engagement with Digital Media: Are They Really Competent? - Nur Laili Noviani; Nur Laili Mardhiyani Mardhiyani; Adison Adrianus Sihombing; Moch Lukluil Maknun; Girindra Putri Ardana Reswari (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Digital literacy is one of the essential skills for students in this digital age to improve their academic performance. Digital media can be used to support learning in daily school life, so both of teachers and students must be competence in the digital world. Even mobile/digital games can be used as one of the learning tools. The Ministry of Communication and Information Technology and the Ministry of Religious Affairs have joined hands to improve the digital literacy of students, especially in madrasas. However, there are no previous studies that provide us with the digital literacy of madrasa students. The aims of this study are to find out and analyze the digital literacy index of madrasa students and also their engagement with digital media. The research was conducted in MTsN in Semarang using an offline survey and the result is analysed using descriptive quantitative method. The result shows that their digital literacy is at high/good level. Students are involved in the digital world because their daily activities can’t be separated from technology and digital media. The result reflects that today’s students are considered as digital native generation whose their life development is highly influenced by digital world. In this case, knowing the digital literacy index becomes an urgent and fundamental matter